Faktor-faktor Yang Berhubungan dengan Kelelahan Kerja Pada Karyawan di Puskesmas Jatiluhur Bekasi - Siti Nurohma; Agustina Agustina (STIKes Persada Husada Indonesia, 2023)
Currently, health problems have become a necessity for all groups of people, because of the increasing standard of living today, the demands for quality health services are also increasing. Decrease in productivity and work capacity as well as health and body defense capabilities that cause work accidents. Fatigue is also a major cause of work accidents and will affect productivity. The purpose of this study was to determine the relationship between work fatigue in employees at the Jatiluhur Health Center in 2022. This study was an analytical method using a Cross Sectional approach. The population in this study were employees at the Jatiluhur Health Center, totaling 67 people. The method used in sampling is total sampling. There is a significant relationship between work fatigue in the working period with P value = 0.05 < (0.05), and Workload P value = 0.05 < (0.05). This study is in line with the results of Nor Andini's research entitled Factors Related to work fatigue in Employees at the Banua Padang Health Center.